Deleuze : empirismo transcendental - Silveira, Felipe Fortes (2019)
This work aims to present and develop an analysis of what Gilles Deleuze (1925-1995) calls his philosophy: a "transcendental empiricism". Our hypothesis is that Deleuze's "superior empiricism" proposes a new conceptual rearticulation between the empirical and the transcendental field, seeking to attain the genesis of real experience and to push the limit experimentation of the intensive thresholds, breaking with the dogmas of representative and hilemorfist thinking , trapped in the forms of identity and the possible, thereby losing the movement by which "data are given as diverse", that is, the process by which the generative events take shape and constitute the real. We seek to unfold these criticisms, and to understand the main contributions that this new empiricism provides.